Correction: MOF-71 as a degradation product in single crystal to single crystal transformation of new three-dimensional Co(ii) 1, 4-benzenedicarboxylate. Issue 4 (7th January 2016) - Chisca, Diana; Croitor, Lilia; Petuhov, Oleg; Coropceanu, Eduard B.; Fonari, Marina S.
Abstract : Abstract : Correction for 'MOF-71 as a degradation product in single crystal to single crystal transformation of new three-dimensional Co(ii ) 1, 4-benzenedicarboxylate' by Diana Chisca et al., CrystEngComm, 2016, 18, 38–41.